The competitiveness of SMEs in the environmental industry in the State of Chihuahua - Díaz González, Helí Hassan; López García, Arturo Cesar; Escobedo Portillo, Alberto (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In a world facing an increasing number of environmental issues, this paper seeks to demonstrate the growing need for environmental goods and services supply in the different regions, as well as to provide an overview of the competitiveness and growth of SMEs in Chihuahua City, Mexico, focused on this sector. Based on the construction of a study sector by means of statistical data, the analysis of SMEs policy regulations and the perspective of actors that are part of the region.